The short evaluation of orofacial myofunctional protocol (ShOM) and the sleep clinical record in pediatric obstructive sleep apnea - Corrêa, Camila de Castro; Weber, Silke Anna Theresa [UNESP]; Evangelisti, Melania; Villa, Maria Pia (Elsevier, 2020)
Introduction: Multiple anatomic and functional risk factors contribute to Obstructive Sleep Apnea (OSA) in children, most of the screening tools only evaluate clinical symptoms. The aim was to describe the evaluation of the short orofacial myofunctional protocol (ShOM) in OSA children, and to analyze if the inclusion of orofacial myofunctional aspects would influence the screening sensitivity/specificity of the Sleep Clinical Record (SCR). Methods: Children from Brazil and Italy with sleep disordered breathing were evaluated by full night polygraphy, the SCR and the ShOM. For the analysis of the correlations, we normalized the distribution of the children based on the percentiles of the Apnea and Hypopnea Index (AHI). The children were divided in: Group1: first percentile AHI up to25% (cut-off value: AHI≤1.9); Group 2: second percentile from 25% to 75% (cut-off values: 1.9˂AHI≤7.9); Group3: third percentile AHI˃75% (cut = off value: AHI˃7.9). The findings of SCR and ShOM were compared for each group. ROC curve of the sensitivity and specificity of OSA diagnosis were compared for SCR alone and the combined results of SCR plus ShOM. Results: 86 children, 47 girls, 4–11 years, were included, 34 children were obese and 20 overweight. OSA severity and obesity showed a positive correlation (p = 0.04). Mean ShOM score was 5.64 ± 2.27, with a positive correlation to the SCR (p = 0.002). In Group1, the SCR showed more nasal obstruction, arched palate and OSAS score/positive Brouilette questionnaire and the ShOM scored more alterations to breathing mode, breathing type (p = 0.01) and lip competence. In Group 3, we found more tonsillar hypertrophy, Friedman tongue position alteration (p < 0.001), malocclusion and obesity at SCR and more alterations in tongue resting position, tongue deglutition position and malocclusion at ShOM. Conclusions: The myofuntional evaluation contributed to the screening of OSA in children, while alterations of the tongue (resting and deglutition position) were observed in children with the highest AHI percentile. The combination of SCR and ShOM improved the sensitivity and specificity for the identification of pediatric OSA when compared to SCR alone.
Keywords: Children; Diagnostic Techniques and procedures; Facial muscles; Obstructive; Sleep apnea; Sleep clinical record; Stomatognathic system